Ecological Responses to Threats in an Evolutionary Context: Bacterial Responses to Antibiotics and Butterfly Species’ Responses to Climate Change - Fitzsimmons, James (Université d'Ottawa / University of Ottawa, 2013)
Humans are generally having a strong, widespread, and negative impact on nature. Given the many ways we are impacting nature and the many ways nature is responding, it is useful to study responses in an integrative context. My thesis is focused largely (two out of the three data chapters) on butterfly species’ range shifts consistent with modern climate change in Canada. I employed a macroecological approach to my research, drawing on methods and findings from evolutionary biology, phylogenetics, conservation biology, and natural history. I answered three main research questions. First, is there a trade-off between population growth rate (rmax) and carrying capacity (K) at the mutation scale (Chapter 2)? I found rmax and K to not trade off, but in fact to positively co-vary at the mutation scale. This suggests trade-offs between these traits only emerge after selection removes mutants with low resource acquisition rates (i.e., unhealthy genotypes), revealing trade-offs between remaining genotypes with varied resource allocation strategies. Second, did butterfly species shift their northern range boundaries northward over the 1900s, consistent with climate warming (Chapter 3)? Leading a team of collaborators, we found that most butterfly species’ northern range boundaries did indeed shift northward over the 1900s. But range shift rates were slower than those documented in the literature for more recent time periods, likely reflecting the weaker warming experienced in the time period of my study. Third, were species’ rates of range shift related to their phylogeny (Chapter 3) or traits (Chapter 4)? I found no compelling relationships between rates of range shift and phylogeny or traits. If certain traits make some species more successful at northern boundary range expansion than others, their effect was not strong enough to emerge from the background noise inherent in the broad scale data set I used.
Keywords: biodiversity; climate change; butterflies; Canada; antibiotic resistance; macroecology; Lepidoptera; phylogenetic signal; species range shifts